Assessing the Reality of Teaching English Online in the First Three Basic Grades from the Point of View of the Teachers in Ain Al-Basha Directorate of Education - Seif, Hanan Ahmed Jaber; Abu Sneina, Odeh AbdAlGawad (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to assess the reality of teaching the English language courses online to the students of the first three basic grades from the point of view of female teachers in Ain Al-Basha Directorate of Education in terms of some variables (educational sector, qualification, years of experience).To achieve the objectives of the study, the descriptive survey approach was used, through the distribution of questionnaires. The population of the study consisted of the female teachers of the first three grades in Ain AL- Basha Directorate of Education during the school year 2021/2022.The sample of the study was selected randomly. It consisted of 120 female English teachers: 80 female teachers from government schools and 40 female teachers from private schools of the Directorate of Education in Ain Al-Basha to measure the reality of teaching English courses online. The data were analyzed using the SPSS program.The results show that the English courses were taught online to the students of the first three basic grades from the point of view of female teachers in Ain Al-Basha Directorate of Education was medium with a mean of3.08. They also show no statistically significant differences in relation to the variables (educational sector, qualification years of experience). The study recommended conducting more studies on the variables of the current study and linking them with other variables in different environments. The study also recommended the necessity of giving female teachers training courses to teach English more efficiently.